Immunocompetence based scoring index for evaluating disease resistance status in indigenous and exotic breeds of chicken - KUNDU, A; SINGH, D P; MOHAPATRA, S C (The Indian Journal of Animal Sciences, 2016)
Birds (433) of both sexes developed from 8 genetically diverse lines of chickens like Aseel, Kadakanath, Naked Neck and Frizzle fowl along with imported breeds Dahlem Red, White Leghorn, Synthetic Dan Line broiler (SDL) and Naked Neck broiler (NNB) were evaluated for immunocompetence traits, viz. haemagglutinin test (HA), mercaptoethanol resistant (MER or IgG), classical pathway (CPW) and alternate pathway (APW) response to sheep red blood cells (SRBCs) at 0, 5, 12 and 19 days post immunization (pi), CMI response (as foot index against PHA-P), phagocytic index (PI) using carbon clearance test. Per cent mortality was also recorded based on whole hatch from which sample birds were drawn for each group from 0–20 weeks of age. Based on the results of immunocompetence traits, a scoring index was formed and various genotypes were ranked. Dahlem Red exhibited highest HA response followed by indigenous breeds. SDL broilers and White Leghorns ranked lowest for HA response. Dahlem Red excelled all other genetic stocks for IgG, FI and only next in order to Aseel and Kadakanath for CPW and APW. The index was constructed giving equal weightage to each of the traits. Broilers and White Leghorns, which ranked lowest, exhibited highest mortality.